2004
DOI: 10.1023/b:pham.0000041459.63362.6f
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Skin Irritation of Lysine-Derivative Anionic Surfactants Using Mouse Fibroblasts and Human Keratinocytes as An Alternative to Animal Testing

Abstract: Purpose. The aim of this study was to identify new surfactants with low skin irritant properties for use in pharmaceutical and cosmetic formulations, employing cell culture as an alternative method to in vivo testing. In addition, we sought to establish whether potential cytotoxic properties were related to the size of the counterions bound to the surfactants.Methods. Cytotoxicity was assessed in the mouse fibroblast cell line 3T6, and the human keratinocyte cell line NCTC 2544, using the MTT assay and uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 22 publications
3
36
0
1
Order By: Relevance
“…These findings show that an increased in surfactant concentrations also caused membrane disruption within the pH range characteristic of early endosomes. However, these concentrations may present toxic effects, as determined by the cytotoxicity assays performed in the 3T3 fibroblast cell line (data shown in section 3.6), and also as reported in previous cytotoxicity studies in 3T6 fibroblasts and NCTC 2544 keratinocyte cell lines [25].…”
Section: Ph-dependent Hemolysissupporting
confidence: 71%
See 2 more Smart Citations
“…These findings show that an increased in surfactant concentrations also caused membrane disruption within the pH range characteristic of early endosomes. However, these concentrations may present toxic effects, as determined by the cytotoxicity assays performed in the 3T3 fibroblast cell line (data shown in section 3.6), and also as reported in previous cytotoxicity studies in 3T6 fibroblasts and NCTC 2544 keratinocyte cell lines [25].…”
Section: Ph-dependent Hemolysissupporting
confidence: 71%
“…1). These surfactants were synthesized in our laboratory as previously described [25,29]. The commercial anionic surfactant sodium dodecyl sulfate (SDS) was used as reference compound.…”
Section: Surfactants Testedmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge about the cytotoxicity and potential mechanisms of surfactant interaction with healthy and tumor cells may help on the development of specific and effective devices for cancer therapy. In previous studies, we identified a number of toxic effects of this class of surfactants (Sanchez et al, 2004(Sanchez et al, , 2006a(Sanchez et al, , 2006b). Nevertheless, given that no single in vitro assay has the capacity to mimic all events that occur in vivo, and in order to complete these toxicological studies, here we performed a comparative evaluation using six cell types and two cytotoxicity assays, MTT and NRU.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The same research group has also explored some lysine-derived surfactants, including N a ,N e -dioctanoyl-lysine, which performed significantly better than classical anionic surfactants in terms of ocular and skin irritancy, haemolytic activity, antimicrobial properties, and aquatic toxicity. [31][32][33][34][35][36] The wide potentialities of lysine-based double-chain anionic amphiphiles as bio-and ecofriendly surfactants with prospective industrial interest prompted us to explore alternative methods for their preparation. Synthetic methodologies were developed to give high yields at a multigram scale and involve inexpensive, safe, simple, and high-yield experimental procedures, as these are key factors for a feasible industrial development of novel surfactants.…”
Section: Introductionmentioning
confidence: 99%